THE INFLUENCE OF WORK FACILITIES AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT TOHU SRIJAYA WOOD CRAFTS UD, BATU CITY - Nunuhitu, Henry El Johanes Dwiputra (Ma Chung Press, 2024)
The purpose of this study was to determine and analyze the effect of facilities and work environment on the performance of employees at UD. Tohu Srijaya wood art. The assumption that the condition of the facilities and work environment is directly proportional to employee productivity. The aim of this research is to formulate and see how big the correlation is between the two variables in relation to the work situation of employees in the production department. The method used in this study is a quantitative method, namely analysis based on accurate data, which is then processed according to the needs of the research variables. The population in this study were all employees at UD. Tohu Srijaya Wood Crafts. The sample in this study used a saturated sample of 33 people. Data collection techniques in this study used questionnaires and observation techniques. In this study, SPSS (Statistical Package for the Social Sciences) software was used for data processing. The results of this study indicate that work facilities have a significant influence on employee performance and the work environment has a significant influence on employee performance at UD. Tohu Srijaya wood art. The research is expected to be able to become the basis for determining policies related to work facilities and conducive working conditions, as well as helping to provide a verifiable basis for further research on the relationship of the work environment to work productivity.